Die Waage von Deventer (1528) als Handelshalle (Bulletin KNOB, 1994)
The incorporation of functional details of a building in relation to the art-historical and architectural-historical approach may lead to surprisingly new insights. The 'Waag' (Weighhouse) in Deventer is a good example of this. For centuries people have been amazed at its extraordinary size and its rich building forms in comparison with other representatives of this architectural type. In connection with this, certain similarities with town halls and commercial halls were already observed on the basis of external characteristics, however, the comparison was not pursued any further.The concept of 'waag' (place for weighing) is not only used for the type of building, but can also refer to weighing as an action which could be performed at a particular place. For instance, it was possible to do so in the town hall or in the commercial hall; in the latter case in some regions the entire building was exclusively named after its weighing function. The same hypothesis is to be assumed and reasoned with reference to the Weighhouse in Deventer.In the first place, it is the dominance of the Deventer Weigh house in connection with the architectural surroundings that reminds one of a town hall or commercial hall. For as a rule, weigh houses are smaller and usually more incorporated into the surrounding buildings, that is the surrounding facades. Furthermore, this also refers to the decoration of the building in question, with symbolical elements from fortress-architecture, such as the bay towers and stairwell tower.Finally, in the decoration of the facade the attention is drawn to the higher-situated parts, whereas the ground Moor with the weigh house has been kept rather flat. However, the above-described elements are characteristic of a commercial hall. What also applies to this type of building is that the ground floor had to be utilized for stacking as well as for weighing goods. That is why they were always carried inside. This comparable multifunctional use also applied to the upper floors. During the Deventer annual fairs accommodation on the upper floors was rented out to the traders.At other times, the upper floors could be furnished as party halls or otherwise used for urban representative purposes. All this is to be seen as the result of the separation between the commercial function and the old, multifunctional town centre where the clerical department of the town continued to be situated. This was probably caused by the development of important annual fairs in Deventer, which had reached their peak in the early 16th century. The size of the building reflects the volume of trade, thus fitting in with a large series of town halls and commercial halls in small towns. Within this group, the town of Deventer tried to demonstrate its special position in the region.The history of the use of the building was further characterized by the decline of Deventer as a commercial town as a result of the Eighty Years' War. For instance, the extension to the steps which date back to 1643 indicates a change in functions in the direction of representation at the expense of trade. After the weighing function had been abolished at the end of the 19th century, the building required a completely different purpose, so that hardly any traces were left of its original use. Comparison shows that typologically the building is to be regarded as a commercial hall in medieval tradition rather than as the oldest weighhouse in The Netherlands.